Оцінка збереженості жиру акули катран - Сидоренко, Олена Володимирівна; Боліла, Надія Олександрівна; Форостяна, Нінель Петрівна (НТУ "ХПІ", 2017)
Досліджено показники, що характеризують збереженість ліпідів чорноморської акули за комплексом фізичних, структурно-механічних та фізико-хімічних методів. Об’єктивна оцінка споживної цінності жиру з печінки акули катран проводилась за умов низькотемпературного зберігання та охолодження порівняно з іншими видами риб. Фізичними методами визначено концентрацію молекул жиру в одиниці об’єму, радіус та об’єм самих молекул жиру для різних видів риб. Оцінка структурно-механічних показників передбачала визначення густини та в’язкості жиру в кореляції з кислотним та перекисним числом.

Integrated and rational processing of raw materials involves the most complete use of organs and tissues of hydrobionts, which ensures the first generation of food products, as well as forage, technical and special purpose. In many countries, dogfish is a promising raw material for the food industry. However, the expediency of using the domestic Black Sea dogfish for food production requires the necessity of systematic studies of dimensional-mass characteristics, morphological characteristics, chemical composition, structural-mechanical, physical, and rheological properties, etc. The purpose of the study is to assess the survival of the dogfish liver Oil through the determination of the basic physical and physicochemical indices of the Oil of the Black Sea dogfish, which characterize its biological efficiency and quality changes during storage. The subject of the study is the Oil from the liver of dogfish, comparing with the Oils from the cod and salmon liver. The technology of obtaining the Oils from the cod and salmon liver involves the application of the cold pressing method we developed with the addition of the kitchen salt. The investigated product meets the established requirements for the content of free fatty acids of fat, which is characterized by an acid number. The method of gas chromatography was used to determine the fatty acid composition of the Oils from the cod and salmon liver. The analysis of the fatty acid composition shows that in the selected Oils from the cod and salmon liver is dominated by monounsaturated fatty acids that act as a source of energy. By calculation, the molar mass of Oils from the cod and salmon liver is 285,8326 g / mol. Molar mass is an important characteristic that should be taken into account when modeling the storage, transport or processing of fish oil. Thus, it has been established that the lowest density of the molecule has fat from the shark of a low-temperature storage catrrane. The mass of a drop of all fats in the range of 0,0225-0,0226 х10-3 kg.
Evaluation of cleaning of dogfish liver oil
Keywords: жир риб'ячий; маса молярна; кислота; радіус молекули; fish oil; molar mass; acid; radius of molecules